Integrated assessment of lateral flow, density effects and dispersion in aquifer storage and recovery - Ward, J.D.; Simmons, C.T.; Dillon, P.J.; Pavelic, Paul (Elsevier, 2009)
Aquifer storage and recovery (ASR) involves the injection of freshwater into an aquifer for later recovery and use. This paper investigates three major factors leading to reduction in performance of ASR systems in brackish or saline aquifers: lateral flow, density-driven flow and dispersive mixing. Previous analyses of aquifer storage and recovery (ASR) have considered at most two of the above processes, but never all three together, and none have considered lateral flow and density effects together. In this analysis, four dimensionless parameters are defined to give an approximate characterisation of lateral flow, dispersive mixing, mixed convection (density effects during pumping) and free convection (density effects during storage). An extensive set of numerical models spanning a wide parameter range is then used to develop a predictive framework using the dimensionless numbers. If the sum of the four dimensionless numbers (denoted RASR) exceeds 10, the ASR operation is likely to fail with no recoverable freshwater, while if RASR < 0.1, the ASR operation is likely to provide at least some recovery of freshwater. The predictive framework is tested using limited data available from ASR field sites, broadly lending support to the framework. This study has several important implications. Firstly, the lack of completeness of field data sets in the literature must be rectified if we are to properly characterise mixed-convective flow processes in ASR operations. Once data are available, the dimensionless numbers can be used to identify suitable ASR sites and the desirable operational conditions that maximise recovery efficiencies.